2020
DOI: 10.1155/2020/7321873
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Trauma and Receipt of Its Treatment among Male School Children in the Eastern Province of Saudi Arabia

Abstract: Background. Dental trauma is a common dental public health problem, and it affects 20% to 30% of permanent dentition worldwide. Objective. To evaluate self-reported dental trauma to permanent anterior teeth and the receipt of dental treatment among male school children. Materials and Methods. This cross-sectional study included grade 7 to 9 school children in Dammam/Al-Khobar, the Eastern Province of Saudi Arabia. The participants responded to a pilot-tested self-completion questionnaire which contained questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 25 publications
1
27
1
Order By: Relevance
“…This result is comparable to different studies conducted in India [ 20 ], Brazil [ 21 ], Turkey [ 22 ], Canada [ 11 ], and Albania [ 23 ], on similar age groups. However, this proportion is higher than the 6.1% reported by Noori et al in Irak [ 24 ], the 6.4% reported by Naidoo et al in South Africa [ 25 ], and is interestingly lower than the 36% reported in Iran [ 26 ], 14.4% reported in India [ 27 ], the 37.9% reported in Chile [ 28 ], the 35.0% reported in Thailand [ 29 ] and the 39.5% reported in Saudi Arabia [ 30 ]. This wide divergence in the results could be attributed to many factors such as the study design, the inclusion/exclusion criteria, the sample size, the sampling procedure, the adopted diagnostic criteria, the chosen age groups, and the cultural and behavioral profile of each country.…”
Section: Discussionmentioning
confidence: 79%
“…This result is comparable to different studies conducted in India [ 20 ], Brazil [ 21 ], Turkey [ 22 ], Canada [ 11 ], and Albania [ 23 ], on similar age groups. However, this proportion is higher than the 6.1% reported by Noori et al in Irak [ 24 ], the 6.4% reported by Naidoo et al in South Africa [ 25 ], and is interestingly lower than the 36% reported in Iran [ 26 ], 14.4% reported in India [ 27 ], the 37.9% reported in Chile [ 28 ], the 35.0% reported in Thailand [ 29 ] and the 39.5% reported in Saudi Arabia [ 30 ]. This wide divergence in the results could be attributed to many factors such as the study design, the inclusion/exclusion criteria, the sample size, the sampling procedure, the adopted diagnostic criteria, the chosen age groups, and the cultural and behavioral profile of each country.…”
Section: Discussionmentioning
confidence: 79%
“…The number of patients included in oral and dental trauma studies was 2,454 (Table 5 ) [ 42 45 ]. There was a comparable proportion of males to females [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was a comparable proportion of males to females [ 43 , 44 ]. While the other two were conducted solely in males [ 42 , 45 ]. Falls were the most common cause of dental injuries (62.7%) [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations